The responsibility to rebuild Mali between reality and challenges - Na'aima, Maidi; Murad, Quraibeez (Journal of Legal and Political Studies, 2020)
War and conflicts have been a source of growing concern and concern even after they have ceased to be caused by disasters and consequences at all levels. hats a lot of challenges .Therefore, the post-conflict phase, wars and the resulting interventions have attracted attention to find ways to get states out of the cycle of return to stability and promote them from the consequences and restructuring of their institutions and strengthen their development. This strategy is called peace-building, which is one of the levels of the principle of responsibility for protection that the United Nations has sought to implement in the state of Mali after the deterioration of the security situation, yet this strategy has experienced many challenges.
Keywords: Responsibility; Rebuild; Mali; Conflicts; PeaceBuilding